Observations of Shallow Methane Bubble Emissions From Cascadia Margin - Michel, Anna P. M.; Preston, Victoria L.; Fauria, Kristen E.; Nicholson, David P. (Frontiers in Earth Science, 2021)
Open questions exist about whether methane emitted from active seafloor seeps reaches the surface ocean to be subsequently ventilated to the atmosphere. Water depth variability, coupled with the transient nature of methane bubble plumes, adds complexity to examining these questions. Little data exist which trace methane transport from release at a seep into the water column. Here, we demonstrate a coupled technological approach for examining methane transport, combining multibeam sonar, a field-portable laser-based spectrometer, and the ChemYak, a robotic surface kayak, at two shallow (<75 m depth) seep sites on the Cascadia Margin. We demonstrate the presence of elevated methane (above the methane equilibration concentration with the atmosphere) throughout the water column. We observe areas of elevated dissolved methane at the surface, suggesting that at these shallow seep sites, methane is reaching the air-sea interface and is being emitted to the atmosphere.